Intervention of trans radial band in reducing the risk of bleeding (hematoma) in patient post percutaneous coronary intervesion in King Saud Medical City - Marlinda Ismiati (lppm Universitas Muhammadiyah Semarang, 2022)
Cardiac catheterization is a procedure to diagnose and evaluate coronary arteries. At the end of the procedure, the radial sheath was removed and pressure was applied both manually and mechanically to the radial artery to control bleeding until hemostasis was achieved. Inadequate compression technique on the access site of the radial artery can result in haemorrhage, hematoma, pseudo aneurysm, radial artery occlusion, and tissue ischemia. Complications of hematoma are often encountered in post-PCI patients with the method of manually applying pressure/compression to the area after the trans-radial puncture followed by a feeling of discomfort for the patient after the PCI procedure. This study aims to see the effectiveness of the TR Band as an alternative to manual compression in reducing the risk of bleeding (hematoma) in the radial artery and increasing patient comfort by using the TR Band. This case study design uses a descriptive approach to nursing care with 1 respondent with inclusion criteria for clients aged over 18 years, clients after percutaneous coronary intervention (PCI) using radial access, clients using TR Bands, clients who do not have hearing loss, can communicate verbally and cooperatively, clients with stable hemodynamic conditions after PCI, clients with normal blood coagulation laboratory results, clients receive heparin anti-coagulation of at least 5,000 IU.TR Band is carried out for 1 shift with a time of 165 minutes. Measurement of the hematoma scale after cardiac catheterization with radial access using the EASY TRIAL and the use of an oxygen saturation measurement tool (pulse oximetry). The results of this case study show that complications of hematoma with Trans Radial Band intervention in patients after cardiac catheterization did not occur. Trans Radial Band intervention is effective in reducing the risk of bleeding (hematoma) in patients after catheterization.